Structure-activity relationships of tubulysin analogues. Issue 14 (15th July 2020) - Courter, Joel R.; Hamilton, Joseph Z.; Hendrick, Nathaniel R.; Zaval, Margo; Waight, Andrew B.; Lyon, Robert P.; Senter, Peter D.; Jeffrey, Scott C.; Burke, Patrick J.
Graphical abstract: Abstract: The tubulysins are an emerging antibody-drug conjugate (ADC) payload that maintain potent anti-proliferative activity against cells that exhibit the multi-drug resistant (MDR) phenotype. These drugs possess a C-11 acetate known to be hydrolytically unstable in plasma, and loss of the acetate significantly attenuates cytotoxicity. Structure-activity relationship studies were undertaken to identify stable C-11 tubulysin analogues that maintain affinity for tubulin and potent cytotoxicity. After identifying several C-11 alkoxy analogues that possess comparable biological activity to tubulysin M with significantly improved plasma stability, additional analogues of both the Ile residue and N -terminal position were synthesized. These studies revealed that minor changes within the tubulin binding site of tubulysin can profoundly alter the activity of this chemotype, particularly against MDR-positive cell types.